Kajian Rekabentuk pembungkusan produk tempe - Ramli, F. (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This thesis is focusing on the product packaging of tempe. This scope area is in the Kuching City. This research is done to design and develop tempe's packaging on the element of graphic design.